Being Single in Georgian England Families, Households, and the Unmarried - Harris, Amy (Oxford University Press, Incorporated, 2023)
Being Single in Georgian England explores what eighteenth-century family life looked like, and how it was experienced, when viewed from the perspective of unmarried and childless family members, explored through the lens of three generations of the famous musical and abolitionist Sharp family